The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1007/s10038-003-0101-8
|View full text |Cite
|
Sign up to set email alerts
|

Hypercholesterolemia associated with splice-junction variation of inter-α-trypsin inhibitor heavy chain 4 (ITIH4) gene

Abstract: Factors predisposing to the phenotypic features of higher total cholesterol (T-Cho) have not been clearly defined. Here we report an association between a C/T single nucleotide polymorphism at IVS17+8 in the inter-alpha-trypsin inhibitor heavy chain 4 gene (ITIH4) and plasma total cholesterol levels in 351 adult individuals from an east-central area of Japan. Age and gender-adjusted levels of plasma T-Cho, LDL-cholesterol, triglyceride, and HDL-cholesterol were analyzed. When we separate the subjects into two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Finally, we used the online annotation tool SnpNexus (Dayem Ullah et al , 2012 ) to annotate the pQTLs as disease SNPs. We found that two of the pQTLs are associated with the following diseases: rs1801020 on gene F12 with cardiovascular disease (Santamaria et al , 2004 ; Cochery-Nouvellon et al , 2007 ) and rs2071042 on gene ITIH4 with hypercholesterolemia (Fujita et al , 2004 ). In summary, we found pQTLs for 13 proteins that explained about 8.5% of the protein-level variance.…”
Section: Resultsmentioning
confidence: 94%
“…Finally, we used the online annotation tool SnpNexus (Dayem Ullah et al , 2012 ) to annotate the pQTLs as disease SNPs. We found that two of the pQTLs are associated with the following diseases: rs1801020 on gene F12 with cardiovascular disease (Santamaria et al , 2004 ; Cochery-Nouvellon et al , 2007 ) and rs2071042 on gene ITIH4 with hypercholesterolemia (Fujita et al , 2004 ). In summary, we found pQTLs for 13 proteins that explained about 8.5% of the protein-level variance.…”
Section: Resultsmentioning
confidence: 94%
“…Interestingly, PDK4 has also been found to be under selection in another aquatic mammal, the walrus [ 18 ]. Another gene with a related metabolic function is AGL , involved in glycogen degradation [ 45 , 46 ]. Genes potentially linked to obesity may be related to the hippo's comparatively large size and capacity for fat storage, although the physiology of hippos in general remains little explored [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…In 2000, Japanese scholar Choi-Miura et al found that inter-alpha-trypsin inhibitor family heavy chain-related protein (IHRP) could inhibit the aggregation and phagocytosis of actins in polymorphonuclear leukocyte, implying that IHRP might be a new APP involved in inflammatory responses [51]. In 2004, Fujita et al showed that genetic locus mutation of ITIH4 might be one of possible factors for dyslipidemia [52]. Then, Piñeiro et al proved that ITIH4 was a new APP isolated from cattle during experimental infection [53].…”
Section: Discussionmentioning
confidence: 99%